2007
DOI: 10.1095/biolreprod.106.055244
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells Derived from Human Fetal Membranes Display Multilineage Differentiation Potential

Abstract: The amnion is the inner of two membranes surrounding the fetus. That it arises from embryonic epiblast cells prior to gastrulation suggests that it may retain a reservoir of stem cells throughout pregnancy. We found that human amniotic epithelial cells (hAECs) harvested from term-delivered fetal membranes express mRNA and proteins present in human embryonic stem cells (hESCs), including POU domain, class 5, transcription factor 1; Nanog homeobox; SRY-box 2; and stage-specific embryonic antigen-4. In keeping wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
353
2
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 385 publications
(382 citation statements)
references
References 46 publications
20
353
2
7
Order By: Relevance
“…Cells were cryopreserved in fetal bovine serum (FBS; Gibco) containing 10% dimethyl sulfoxide. Cells displaying typical cobble stone epithelial morphology in culture and > 98% positive for the epithelial markers cytokeratin 7 and 8/18 (Dako, Glostrup, Denmark) were used in subsequent experiments [20,33].…”
Section: Isolation Of Haecmentioning
confidence: 99%
See 3 more Smart Citations
“…Cells were cryopreserved in fetal bovine serum (FBS; Gibco) containing 10% dimethyl sulfoxide. Cells displaying typical cobble stone epithelial morphology in culture and > 98% positive for the epithelial markers cytokeratin 7 and 8/18 (Dako, Glostrup, Denmark) were used in subsequent experiments [20,33].…”
Section: Isolation Of Haecmentioning
confidence: 99%
“…HLC were differentiated from hAEC in a similar manner as previously reported [20,22], except for the addition of HepG2-conditioned medium. Studies have shown that when hAEC were co-cultured with mouse hepatocytes expression of albumin, a1 anti-trypsin, and cytochrome P450 enzyme was increased [25].…”
Section: Properties Of Encapsulated Hepatocyte-like Cells 871mentioning
confidence: 99%
See 2 more Smart Citations
“…About 100-200 million of human amnion epithelial cells (hAECs) can be harvested from term placenta, which is generally discarded after birth (Murphy et al 2010) and instead could represent an important source of potential regenerative tissue. In vitro studies have shown that hAECs can develop into various cell lines, such as cardiomyocytes, myocytes, osteocytes, adipocytes, pancreatic cells, hepatocytes, as well as neural and astrocytic cells (Miki et al 2005;Ilancheran et al 2007). The hAECs pluripotency makes them suitable in treating disorders of the nervous system.…”
Section: Fetal Annexes-derived Mscsmentioning
confidence: 99%